2008
DOI: 10.1007/s10661-008-0430-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies on antioxidant status in Mugil cephalus in response to heavy metal pollution at Ennore estuary

Abstract: Estuaries, the important component of natural environment are under pressure nowadays due to pollution from different sources like industries, agricultural fields etc. Ennore estuary one of the highly polluted estuary situated in Chennai, Tamilnadu, India, due to heavy industrialization surrounding this site poses serious threat to its inhabitants. The present paper focuses on studying the response of the fish Mugil cephalus with reference to its antioxidants during their exposure to metals like iron and chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 16 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…In our study, the activities of Mn SOD, CAT, GSH-Px and GST in the liver were significantly lower at EB in comparison to reference locality PL. Investigations of other authors also show lower SOD and CAT activities in polluted sites, such as in M. cephalus in India [39] and Dentex labrax in Portugal [40]. Contrary to these findings, some studies demonstrated increased activities of these enzymes in polluted environments [41].…”
Section: Resultsmentioning
confidence: 82%
“…In our study, the activities of Mn SOD, CAT, GSH-Px and GST in the liver were significantly lower at EB in comparison to reference locality PL. Investigations of other authors also show lower SOD and CAT activities in polluted sites, such as in M. cephalus in India [39] and Dentex labrax in Portugal [40]. Contrary to these findings, some studies demonstrated increased activities of these enzymes in polluted environments [41].…”
Section: Resultsmentioning
confidence: 82%
“…Due to the rapid industrialization, metal contamination is one of the serious problems that is faced by the Ennore estuary located in North Chennai, Tamilnadu state of India. Heavy metals induce oxidative stress in fish by generating ROS by their participation in Fenton reaction (Padmini et al 2008c). Fish inhabiting the highly polluted Ennore estuary developed an enhanced state of oxidative stress characterized by increased levels of lipid peroxides (LPO), lipid hydroperoxides (LHP), and conjugated diene (CD) when compared to the Kovalam estuary fish in the isolated liver mitochondrial fraction (Padmini and Vijaya Geetha 2007a, b, c).…”
Section: Introductionmentioning
confidence: 99%
“…Pollutants like heavy metals, polycyclic aromatic hydrocarbons (PAH) are found to be the main contaminants of waters of Ennore estuary which contributes to oxidative stress due to their reactive oxygen species generating power (Padmini et al 2008c;Padmini and Vijaya Geetha 2008). Seasonal variation, one of several biological factors have been reported to have a significant influence on estuaries (Wilhelm Filho et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, attempts were made regarding the evaluation of metal pollution, measurement of metalpollution-induced oxidative stress, and the expression of HSP70 in M. cephalus surviving in this polluted estuary (Padmini et al 2008b;Padmini and Usharani 2008). In Ennore estuary fish liver mitochondrial samples, the comparison of LPO values with the result of the TAC values showed that the TAC level decreases proportionately with increased levels of LPO reflecting the defective antioxidant status when compared with Kovalam estuary samples (Table 1 *p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that the fish inhabiting the Ennore estuary are able to survive in the heavy metal pollution induced stressed situation (Padmini et al 2008b). It is important to understand the various damages that occur in these fish liver mitochondria during stress conditions and the mechanism that are involved in providing resistance to such damages which allow the fish to survive.…”
Section: Introductionmentioning
confidence: 99%